Hybrid technology for the use of solar energy : the challenge towards green energy / S. I. Hossain ... [et al.] - Hossain, S. I.; Al-Mamun, M. R.; Sikdar, S.; Al-Amin, M.; Majumder, S. C.; Hasan, M. R.; Khan, M. Z. H. (2015)
Large areas in many countries are populated but have no connection to a national electricity grid. Centralized electricity generating facilities burning fossil fuels have been the normal. Renewable energy resources, especially solar energy is now penetrating this sector. Long-term energy storage is the universal challenge in providing renewables-based electricity with high availability across the seasons. Solar domestic hot water system is widely used and developing fast in recent years. However many problems occur at the same time, for example more energy consumption by circulation pump, water reheating, long investment payback period, and etc. The motivation for the development of a combined hot water and sorption store is to complement the advantages and to reduce the disadvantages of the two particular storage technologies. Hot water stores offer high heat supply rates but are particularly suitable for short term storage due to heat losses whereas for a sorption store the power drain is low but it shows the advantage of a high storage density and long-term heat storage almost without losses. We investigated the demonstration project and discuss the need for authoritative system modelling in order to size the system components for minimum cost at a designated availability of supply.